Asset Management System Application on PT Fineks Utama Based on Web - Sulton, Besus Maulana; Zuraidah, Eva (Forum Kerjasama Pendidikan Tinggi (FKPT), 2021)
Along with the development of Information Technology which is growing rapidly and its wide application to business aspects or fields, information technology has also been widely used by industries or other organizations. Its utilization aims to facilitate users and provide efficiency in a business field in carrying out its activities. Of the many assets currently in the company and the fast transfer of assets from one branch to another, it requires us to optimally be able to carry out a good and clear traceability process. So that existing assets remain well monitored. From the facts, many companies or offices still carry out recording company assets manually using paper or books using the manual logbook method which will result in all asset transactions being recorded in the logbook manually, starting from receipt of asset purchases, asset transfer, depreciation. assets and also asset sales. From these problems, the researcher proposes research as an alternative solution in the form of a web system application building design to replace the function of notebook assets or what is called the Asset Management System Application using a Structured, Design Method, PHP and MYSQL-based approach with website-based application development. The results achieved are expected to be able to improve efficiency and existing rights in managing company assets quickly when managed, the results of this study can also help companies record the depreciation process for their assets, record new assets purchased, manage new and old assets, and the history of asset transfers from one user to another and from one place to another.